Strategi Guru Dalam Pengelolaan Kelas - Siregar, Ehdatul Puadi; Nirwana, Herwan; N, Neviyarni (Madani: Jurnal Ilmiah Multidisiplin, 2024)
School is one of the educational institutions that has a very important role in increasing students' knowledge as students, especially at TPQ Housing Salingka 2 Padang. Sometimes students or students are still not ready to learn when the subject is taking place in class so the teacher is obliged to improve and be responsible so that learning conditions can run in a pleasant atmosphere so that they can always improve students' learning abilities and stimulate students to be motivated to receive lessons, especially subjects. religion subject. Classroom management does not only involve the physical arrangement of the classroom, but also includes managing social interactions and student behavior. Teachers must be able to create a safe and supportive environment, where every student feels valued and respected. This involves the use of disciplined and effective and fair techniques, as well as promoting positive behavior and a good work ethic. Apart from that, classroom management also involves planning and organizing lesson materials. Teachers must be able to design and implement effective learning plans, which include clear learning objectives, interesting and relevant activities, and fair and objective assessments. Classroom management also includes the use of technology in learning. In today's digital era, teachers must be able to utilize technology to improve students' learning experiences, or provide feedback. Overall, classroom management is a complex task that requires a variety of skills and knowledge. However, with practice and dedication, teachers can develop effective classroom management skills, which will ultimately have a positive impact on student learning outcomes.